Tandem MS-Based Metabolite Profiling of 19,20-Epoxycytochalasin C Reveals the Importance of a Hydroxy Group at the C7 Position for Biological Activity - Kushwaha M.; Qayum A.; Jain S.K.; Singh J.; Srivastava A.K.; Srivastava S.; Sharma N.; Abrol V.; Malik R.; Singh S.K.; Vishwakarma R.A.; Jaglan S. (My University, 2025)
Seven cytochalasins, 19,20-epoxycytochalasin N, cytochalasin P1, deacetyl 19,20-epoxycytochalasin C, 19,20-epoxycytochalasin D, 19,20-epoxycytochalasin C, cytochalasin D, and cytochalasin C, were isolated from a fungal (Rosellinia sanctae-cruciana) crude extract. A cytotoxicity assay (sulforhodamine B) was performed on a series of cancer cell lines: HT-29, A-549, PC-3, HCT-116, SW-620, and MCF-7. Simultaneously, the liquid chromatography-mass spectrometry (LC-MS)/MS profile of 19,20-epoxycytochalasin C-treated cell lines revealed that 19,20-epoxycytochalasin C (m/z 524.25) oxidized to a metabolite of m/z 522.25 Da (-2 Da (-2H) from 19,20-epoxycytochalasin C). Further chemical oxidation of 19,20-epoxycytochalasin C using the Dess-Martin reagent produced an identical metabolite. It has been noticed that the parent molecule (19,20-epoxycytochalasin C) showed an IC50 of 650 nM (on HT-29), whereas for the oxidized metabolite (m/z 522.24) of 19,20-epoxycytochalasin C, the IC50 was >10 μM. It is clear that the parent molecule had 16 times higher cytotoxic potential as compared to the oxidized metabolite. The spectroscopic investigation indicated that the oxidation of the hydroxyl (-OH) group occurred at the C7 position in 19,20-epoxycyctochalsin C and led to the inactivation of 19,20-epoxycytochalasin C. Further, cell cycle analysis and histopathological evidence support the findings, and CDK2 could be a possible target of 19,20-epoxycyctochalasin C. © 2021 The Authors. Published by American Chemical Society.